Investigation of the Cu/ferrochromium composite production parameters effects on the electrical conductivity - Yilmaz, Osman; Aksoy, Mustafa; Aydo?du, Yildirim (My University, 1999)
In this study, the effects of production parameters on the electrical conductivity of Cu/ferrochromium composite using as the electrofriction materials for collectors were investigated. %5, 10, 15, 20, 30, 40 ferrochromium were added to Cu powders. The pressure was applied as 380, 635, 955 Mpa to produce samples in the dimension of 79 mm2 and 1 mm thick. Also temperature was changed as 700, 800, 900°C during sintering. Electrical conductivity of samples was measured after sintering. Metallographicaly, to determine microstructure, SEM and EDS analysis were taken. Finally, it was detected that electrical resistivity has been decreased by increasing sintering temperature, compression and increased depending on ferrochromium ratio.
Ferrokrom katkili cu kompozi?ti?n i?letkenli??i?ne üreti?m parametreleri?ni?n etki?si?ni?n araştirilmasi
Ulusal Toz Metalurjisi Konferansi: Second National Powder Metallurgy Conference -- 15 September 1999 through 17 September 1999 -- Ankara -- 62638
Keywords: Composites; Electrical conductivity; Powder metallurgy; Sintering